UNVEILING DISCORD: EXPLORING COMMUNICATION CHALLENGES IN POLYGAMOUS FAMILIES AMONG MALAYSIAN MUSLIMS - Dzulkarnain Mazlan; Asma Md. Isa; Zulkifli Abd Latiff (Journal of Islamic, Social, Economics and Development, 2024)
This paper investigates the issues and challenges faced by polygamous families, specifically focusing on family communication. The study aims to understand the communication dynamics within polygamous families, acknowledging the various issues they face such as economics and mental health. The research is limited to the context of Muslim families practicing polygamy in Malaysia. Using a qualitative research design, the study employed semi-structured interviews with six informants selected through purposeful and snowball sampling. The findings revealed serious miscommunication and lack of communication problems within polygamous families, leading to strained relationships between children and their fathers, as well as between co-wives and their stepchildren. The study emphasizes the negative implications of poor communication in polygamous families, including strained relationships, hostility, mental health issues, and emotional instability. The paper concludes by highlighting the importance of effective communication in mitigating these challenges and promoting healthier family dynamics.